Kinetic Electromagnetic Energy Harvester for Railway Applications-Development and Test with Wireless Sensor - Hadas, Zdenek; Rubes, Ondrej; Ksica, Filip; Chalupa, Jan (Sensors (Basel, Switzerland), 2022)
This paper deals with a development and lab testing of energy harvesting technology for autonomous sensing in railway applications. Moving trains are subjected to high levels of vibrations and rail deformations that could be converted via energy harvesting into useful electricity. Modern maintenance solutions of a rail trackside typically consist of a large number of integrated sensing systems, which greatly benefit from autonomous source of energy. Although the amount of energy provided by conventional energy harvesting devices is usually only around several milliwatts, it is sufficient as a source of electrical power for low power sensing devices. The main aim of this paper is to design and test a kinetic electromagnetic energy harvesting system that could use energy from a passing train to deliver sufficient electrical power for sensing nodes. Measured mechanical vibrations of regional and express trains were used in laboratory testing of the developed energy harvesting device with an integrated resistive load and wireless transmission system, and based on these tests the proposed technology shows a high potential for railway applications.
Keywords: train; vibration; wireless sensor; electromagnetic transducer; model; energy harvesting; test